2009
DOI: 10.1037/a0016136
|View full text |Cite
|
Sign up to set email alerts
|

Effective techniques in healthy eating and physical activity interventions: A meta-regression.

Abstract: ObjectiveMeta-analyses of behavior change (BC) interventions typically find large heterogeneity in effectiveness and small effects. This study aimed to assess the effectiveness of active BC interventions designed to promote physical activity and healthy eating and investigate whether theoretically-specified BC techniques improve outcome. DesignInterventions, evaluated in experimental or quasi-experimental studies, using behavioral and/or cognitive techniques to increase physical activity and healthy eating in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

78
1,860
16
14

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,942 publications
(1,968 citation statements)
references
References 129 publications
78
1,860
16
14
Order By: Relevance
“…It updates previous systematic reviews and metaanalyses of sexual health interventions -the most recently published of which searched papers published up until 2008 (Henny et al, 2012), 2009(Shepherd et al, 2011TolouShams et al, 2010), and 2010 (Lopez et al, 2011). In addition, previous meta-analyses concerned with sexual health have tended to focus on specific issues such as contraceptive use (Lopez et al, 2011) andHIV prevention (Albarracín et al, 2005), or on specific population groups like juvenile offenders (Tolou-Shams et al, 2010) and African American men (Henny et al, 2012).…”
Section: Discussionmentioning
confidence: 70%
“…It updates previous systematic reviews and metaanalyses of sexual health interventions -the most recently published of which searched papers published up until 2008 (Henny et al, 2012), 2009(Shepherd et al, 2011TolouShams et al, 2010), and 2010 (Lopez et al, 2011). In addition, previous meta-analyses concerned with sexual health have tended to focus on specific issues such as contraceptive use (Lopez et al, 2011) andHIV prevention (Albarracín et al, 2005), or on specific population groups like juvenile offenders (Tolou-Shams et al, 2010) and African American men (Henny et al, 2012).…”
Section: Discussionmentioning
confidence: 70%
“…Despite this there was less of a focus on maintenance and relapse prevention. While all but one of the apps used a recognized BCT, none specifically referred to any specific BCT taxonomy [5][6][7][8][9]. Documentation was poor, with only a small number of apps providing adequate descriptions of the theory behind the behavior change techniques employed.…”
Section: Discussionmentioning
confidence: 99%
“…The session titles/topics were as follows: (1) exploring motivators for weight loss/ getting started being active, (2) making wise food and beverage choices, (3) be strategic: three ways to reduce your calories in, (4) reading nutrition labels/ food substitutions, tasting new foods, (5) cutting the budget while cutting calories, (6) taking charge of what's around you, (7) taking charge of what's within you (talking back to negative thoughts), and (8) dealing with slips and staying motivated. Only eight sessions that focused on critical topics to the target population (as opposed to all 16 sessions in the DPP) were included because of challenges to committing to a longer program on the part of WIC participants, as evidenced in our developmental work and literature [4].…”
Section: Methodsmentioning
confidence: 99%
“…These interventions have not used or translated existing evidence-based programs or strategies [5,6] (i.e., limited focus on creating an energy deficit; nonsystematic use of self-monitoring, goal-setting and problem-solving, and limited hands-on opportunities and support to develop healthy cooking skills and physical activity behaviors). In addition, studies reported poor attendance and high attrition rates.…”
mentioning
confidence: 99%